The Effect of Sustained Attention Tasks on Gait Pattern Variations in Children with Attention Deficit-Hyperactivity Disorder: A Clinical Trial Study - Sana Soltani; Abbas Bahram; Farhad Ghadiri; Alireza Farsi (Vesnu Publications, 2021)
Introduction: The current gait profile of children with attention deficit-hyperactivity disorder (ADHD) is incomplete and mainly based on a short-time walking without the involvement of different senses. The aim of this study was to investigate the dual-task gait of ADHD and typically-developed (TD) children while receiving sustained visual-vestibular stimulus.Materials and Methods: 21 children with ADHD and 12 TD children (7-10 years) participated in the study. Participants walked on the treadmill in three self-selected speeds three-minute trials in single-task (without visual instructions) and dual-task (simultaneously following visual-vestibular saccade and smooth pursuit stimuli) conditions. Stride length, global angle of the dominant leg, step width, and the variability of these parameters were assessed using a factor analysis of variance at significant level of α = 0.05.Results: The effect of group-stimulus interaction on stride length was not significant (P = 0.860), but its variability was significant [less variability for typical children compared to children with ADHD (P = 0.001)]. The interactive effects on the global angle were significant (P = 0.001), but its variability was not significant (P = 0.720). In without instruction and in smooth pursuit conditions, significant ankle rotation was observed in children with ADHD (P = 0.001) compared to that of typical children. Step width (P = 0.001) and its variability (P = 0.003) were significantly affected and typical children had wider walking with less variability than the other groups (P = 0.001).Conclusion: Different visual-vestibular instructions can affect the gait of the children with ADHD in various ways. These results can be considered as a basis for the integration of dualistic and synergy models and guidance for educators of children with ADHD.